A new highway in Germany and the impacts on real estate prices - Jeffrey P. Cohen; Sandra Schaffner (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
How does a new highway in Germany impact residential real estate prices - both owner-occupied and rental properties? Construction of the A38 highway was completed in 2009 and expanded by additional interchanges at several points in time, through 2013. The highway connects the east and west of Germany. This dramatically alleviated congestion on nearby roads as well as enhanced connectivity for residents in the mainly rural areas. We consider a hedonic house price model with a quasi-difference-in-differences specification, to test the hypothesis that there are positive price effects on German real estate resulting from the highway completion and the associated relief of nearby road congestion. We control for potential negative effects due to additional noise and pollution, using direct distance (as the crow flies) to the nearest point on the highway. We use a German dataset on rental and owner-occupied real estate prices, for properties listed for sale and rent throughout Germany in the years 2007-2017. The treatment effects for houses and for apartments for rent are positive and significant, which implies that shorter distance to the highway leads to higher prices after the opening of the major highway (A38). The magnitudes of these treatment effects are larger for houses than for apartments. These results imply that the market capitalizes the new highway more strongly for sale properties than for rentals, perhaps because ownership implies a longer term commitment to staying in a property than renting. In other words, the present discounted value of the expected highway benefits over a relatively long time horizon are reflected quite strongly in owner occupied properties. For the changes in 2008 and 2009 we do not observe any significant effects of noise and pollution on prices while there are negative effects in 2012 and 2013. It appears likely that these disamenities became more prevalent in the most recent years.
Keywords: R3; R4; 330; Real Estate Prices; highways; Germany